Linc-ROR Modulates the Endothelial-Mesenchymal Transition of Endothelial Progenitor Cells through the miR-145/Smad3 Signaling Pathway - Liang, J; Chu, H; Ran, Y; Lin, R; Cai, Y; Guan, X; Cui, X; Zhang, X; Li, H; Cheng, M (Physiological research, 2024)
The endothelial-mesenchymal transition (EndMT) of endothelial progenitor cells (EPCs) plays a notable role in pathological vascular remodeling. Emerging evidence indicated that long non-coding RNA-regulator of reprogramming (linc-ROR) can promote epithelial-mesenchymal transition (EMT) in a variety of cancer cells. Nevertheless, the function of linc-ROR in EPC EndMT has not been well elucidated. The present study investigated the effect and possible mechanisms of function of linc-ROR on the EndMT of EPCs. A linc-ROR overexpression lentiviral vector (LV linc-ROR) or a linc-ROR short hairpin RNA lentiviral vector (LV-shlinc-ROR) was used to up or downregulate linc-ROR expression in EPCs isolated from human umbilical cord blood. Functional experiments demonstrated that LV-linc-ROR promoted the proliferation and migration of EPCs, but inhibited EPC angiogenesis in vitro. In the meantime, reverse transcription-quantitative PCR and western blotting results showed that the expression of the endothelial cell markers vascular endothelial-cadherin and CD31 was decreased, while the expression of the mesenchymal cell markers ?-smooth muscle actin and SM22? was increased at both mRNA and protein levels in LV-linc-ROR-treated EPCs, indicating that linc-ROR induced EPC EndMT. Mechanistically, the dual-luciferase reporter assay demonstrated that microRNA (miR/miRNA)-145 was a direct target of linc-ROR, and miR-145 binds to the 3'-untranslated region of Smad3. Moreover, LV-shlinc-ROR increased the expression of miR-145, but decreased the expression of Smad3. In conclusion, linc-ROR promotes EPC EndMT, which may be associated with the miR-145/Smad3 signaling pathway. Keywords: Endothelial progenitor cells, Endothelial to mesenchymal transition, Linc-ROR, MiR-145, Atherosclerosis.
Keywords: signální transdukce; RNA dlouhá nekódující; MicroRNAs; Epithelial-Mesenchymal Transition; mikro RNA; proliferace buněk; Humans; lidé; Endothelial Progenitor Cells; endoteliální progenitorové buňky; RNA, Long Noncoding; Endothelial-Mesenchymal Transition; Cells, Cultured; Cell Proliferation; Smad3 Protein; pohyb buněk; kultivované buňky; endotel-mezenchymální transformace; epitelo-mezenchymální tranzice; Signal Transduction; Cell Movement; protein Smad3